Meningkatkan Hasil Belajar Siswa melalui Penerapan Model Pembelajaran Kooperatif Tipe Snowball Trhrowing pada Mata Pelajaran IPS di Kelas IV SDN 1 Mongkoinit Kabupaten Bolaang Mongondow - Rahmita Hala’a; Yusraningsih H Pongoliu; Yulanti S Mooduto (Journal on Education, 2024)
The problem studied in this research is whether implementing the Snowball Throwing type of cooperative learning model can improve student learning outcomes in social studies class IV Mongkoinit, Bolaang Mongondow Regency. The type of research used in this research is classroom action research with research subjects of 25 class IV students at SDN 1 Mongkoinit. There was an increase in learning outcomes in the first cycle of observing teacher activities by 66.7%, in student activities by 55%, and in student learning outcomes by 56. %. Then in cycle II there was an increase in teacher activity of 91.6%, student activity of 95% and learning outcomes of 88%.